Otimização dos parâmetros de um sistema de comunicação acústica subaquática para minimizar o consumo energético - Souza, Fabio Alexandre de (2016)
In this Thesis, an energy consumption model for underwater acoustic networks is proposed. The model takes into account the specificities of the underwater environment, such as the use of acoustic waves for communication, dependence of the underwater acoustic channel bandwidth with the path loss, which varies with both the distance and frequency, and noise. The fading, usually modeled by Rayleigh and Rice distributions on terrestrial communications, in this work, is modeled by the K distribution, which best represents the severity of the underwater environment. The model considers a linear multi-hop underwater network and the possibility of retransmissions to calculate the total energy consumed for each bit of information successfully transmitted between the source and the destination. In order to obtain the minimum energy, the SNR and the operating frequency are also optimized. The use of convolutional codes is considered and the optimal code rate, which leads to the minimum energy consumption, is determined. A theoretical analysis was developed for two scenarios: delay constrained and delay unconstrained networks, indicating the optimal number of hops which minimizes energy consumption. Next, the impact of the number of transmission trials was considered. A numerical analysis was also performed for both the scenarios. The numerical results validate the theoretical analysis, showing that the multi-hop scheme is more efficient in terms of energy consumption when compared to direct transmission. Furthermore, the results show that a small number of transmission trials is sufficient to achieve a considerable reduction in energy consumption in multi-hop networks, limiting the average delay per packet transmitted, which is very interesting in real applications.